David Miller on Inherited National Responsibility - Pranay Sanklecha (Intergenerational Justice Review)
This paper offers a critique of David Miller's recent account of inherited national responsibility. It is argued that the account leads to a dilemma: either it does not make sense to say that we can accept the national inheritance, or, on a different sense of acceptance, it does, but then we encounter a serious conflict with one of our important intuitions about responsibility.